The Effect of Work Life Balance, Leadership Style, and Workload on the Performance of Employees of the Pompengan River area Office in Jeneberang Case Study - Ryan Riyanto Rachmat; Mansyur Ramly; Ismail H. A (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the influence of work life balance, leadership style, and workload on the performance of generation Z employees at the Pompengan River Area Office in Jeneberang. The research method used is associative research with a quantitative descriptive approach. The research sample consisted of 53 respondents who were Generation Z employees, and data were collected through questionnaires. Data analysis was carried out using multiple linear regression to test the influence of independent variables on dependent variables. The results of the study show that work-life balance has a positive effect on employee performance, which means that the better the work-life balance, the higher the performance shown. Leadership style also has a positive effect, especially if the leader is able to implement a communicative and participatory leadership pattern. On the other hand, workload has a negative effect on employee performance, where a high workload tends to reduce productivity. This study emphasizes that human resource management in the BBWS Pompengan Jeneberang environment needs to pay attention to work balance, the application of an effective leadership style, and proportionate workload management so that the performance of generation Z employees can be optimized.